Ethical Relations of Muslims and Non-Muslims in Creating Culture of Peace at Peace Place Pati in the Perspective of Emmanuel Levinas - Musyafi'in, Farid Naufa; Said, Nur (FIKRAH, 2024)
The existence of religion on Earth has evolved into a means of socially and spiritually regulating norms and achieving harmony in life. Aside from that, humanity comes with racial, ethnic, linguistic, and religious diversity. Human thoughts and feelings evolve to build ethical interactions and empathy with other humans due to these differences. This article aims to demonstrate how Emmanuel Levinas' ethical theory entwines ties between Muslims and non-Muslims to establish nonviolent life training and a culture of peace at Peace Place Pati. For Levinas, ethics is about firsthand experience rather than right and wrong. This article presents field research using a phenomenological approach and a qualitative methodology. According to the study's findings, Muslims are aware of the need to put aside prejudice and listen to non-Muslim groups to build peaceful relationships based on understanding and the provision of a safe place. The significance of diversity and equality awareness in creating a welcoming and peaceful community where everyone is valued and given a place. This research aids in understanding the dynamics of interreligious relations in a particular environment.